New cases to strengthen learning in programming course - Elham Tavakol (Mulia International Journal in Science and Technical, 2018)
Difficult learning methods are currently getting smaller for the public to be interested in, now they have switched how difficult is easy and fun. Information theorists agree that "smart" models are interesting new topics in the field of algorithms, and experts agree. Even though it's usually an unfavorable goal, it's supported by work in the field. In our research, we confirm multi-processor analysis, which embodies the structured principles of e-voting technology. We explore new real-time archetypes, which we call Shaving. The results of this case test are expected to be realized so that it can be applied in all conditions around us.